Patient's satisfaction with a lower limb prosthesis: a longitudinal study - Isaias Pimentel dos Santos; Alana das Mercês Silva; Graziella Santos Furtado; Rosarly Maria Marques de Menezes; Kionna Oliveira Bernardes dos Santos; Daniel Dominguez Ferraz (Universidade de São Paulo, 2021)
ABSTRACT This is a descriptive longitudinal study that aimed to verify prosthesis satisfaction of older adults with lower-limb amputation (LLA). In total, This study was composed of 34 older adults with LLA participated of this study. Participant's satisfaction about the lower-limb prosthesis (LLP), the discomforts, and the embarrassment when use it were evaluated through an interview composed of five questions. The occurrence of falls and the independence in prosthesis management were also evaluated. All variables were collected at the last week of ambulatory rehabilitation discharge and after one and three months. A descriptive and inferential statistical analysis was performed. The level of significance was set at 5% (p <0.05). In total, 80% of participants with transtibial amputation and 78.6% of participants with transfemoral amputation were satisfied with the LLP after three months. Tight prosthesis, walking pain, the embarrassment of using LLP, and the occurrence of falls decreased over time. The independence in prosthesis handling did not change significantly after three months. Participants that used manual locking knee (p=0.040) and/or Solid-Ankle Cushion Heel foot (p=0.017) were more satisfied with LLP. The occurrence of falls reduced (p=0.039) after transfemoral participants started to use the prosthesis. Participant's satisfaction with the LLP was high and did not change significantly over time.